Tongue Flap for Closure of Anterior Palate Fistula - V.K. Puri; Vikram P. Gupta (Indian Journal of Plastic Surgery, 1990)
12 cases of anterior palate fistula larger than 5 mm in diameter were treated by anteriorly based dorsal, midline mucomuscular tongue flap without any fixation of tongue or jaw. The results obtained during the course of study support the method for the closure of large anterior palate fistula following cleft palate surgery.